THE MEDIA DEVELOPMENT OF JOBSHEET ON THE PRACTICE OF MANUAL ELECTRIC WELDING IN THE TENTH GRADE OF TKR SMK KARSA MULYA PALANGKA RAYA 2014/2015 - Ifan Jon Rusadi; Vontas Alfenny Nahan (Jurusan Pendidikan Teknologi Dan Kejuruan, 2016)
Jobsheet is a printed media by which the making process is by printing or offset. This printed media delivers its message through letters and pictures illustrated to make clearer message or information in order for the students to learn independently with or without tutorial. The purposes of this research are: (1) to develop jobsheet media for the practice of manual electric welding for tenth grade of TKR SMK Karsa Mulya Palangka Raya 2014/2015; (2) to describe practice results after learning using jobsheet media developed for manual electric welding; (3) to describe students response on the learning using jobsheet media. Development model used here is procedural model that is a descriptive model that shows steps to be followed to produce certain product. In this research something to be developed is a learning device in a jobsheet of the study material Manual Electric Welding. Instruments to be used is a validation sheet from a material expert, a validation sheet from a media expert, and student response questionnaire. Validation sheet obtained to determine the appropriateness of the media to be used in learning. Based on the research result it can be concluded: (1) development result shows jobsheet can be used in the practice of manual electric welding, and from the material expert it is obtained score 49 with average 4,08 which means good. From the media expert the score is 47 with average 4,7 which means very good. (2) student study results using jobsheet shows all students finish, as per the KKM which is ? 75; (3) student response results on 8 aspects were presented to the students. From the field assesment score 533 is obtained with average 4,16 which means very good. It is then concluded that jobsheet development can be used in learning media.